Clinical intensive care and acute medicine - Hillman, Ken; Bishop, Gillian (Cambridge University Press, 2004)
Focusing on areas common to all critically ill patients, including fluid therapy, sedation, shock, infection and other central topics, this reference to basic pathophysiological principles provides an excellent launch pad for a section on individual disease entities. The text is supported by problem-oriented guidelines to help the care provider tackle real-life practical problems. The new edition reflects the challenges of intensive care medicine, relevant to all residents, trainees, nursing staff and paramedics attached to the ICU. First Edition Pb (1996): 0-521-47812-X
Keywords: Resuscitation; jednotky intenzivní péče; akutní nemoc; Acute Disease; péče o pacienty v kritickém stavu; resuscitace; urgentní lékařství; Emergency Treatment; terapie náhlých příhod; anesteziologie a intenzivní lékařství; Intensive Care Units; Critical Care